퇴행성 요추 질환의 보존적 치료에서 자기공명영상 재촬영의 유효성 - 김주오(Ju-Oh Kim); 박봉주(Bong-Ju Park); 최병완(Byung-Wan Choi); 송경진(Kyung-Jin Song); 최병렬(Byung-Ryeul Choi); 양윤혁(Yun-Hyeok Yang) (The journal of the Korean Orthopaedic Association, 2009)
목 적: 보존적 방법으로 치료 중인 퇴행성 요추 질환 환자에서 초기 MRI와 추시 중 재촬영한 MRI를 비교하여 증상 변화 유무에 따른 자기 공명 영상 소견의 변화 여부를 통해 MRI 재촬영의 의미 및 적응증을 확인해 보고자 하였다. 대상 및 방법: 퇴행성 요추 질환으로 보존적 치료 중 추시 MRI를 측정한 70예의 각각의 MRI에 대하여 추간판, 후관절, 추간공, 신경근, 황색 인대 5 항목에 0, 1, 2, 3의 점수로 초기와 재촬영 MRI 상 변화 정도를 전향적으로 분석하였다. 증상의 변화에 따라 변화가 없었던 I 군(38예)과 통증의 정도가 심해진 II 군(18예), 신경학적 검사 소견이 악화된 III 군(14예)으로 구분하여 추시 MRI 상 병변의 변화 여부를 확인하였다. 결 과: MRI 상 각 항목 당 평균 점수는 처음 추간판 1.76, 추간공 1.31, 후관절 1.79, 신경근 1.71, 황색 인대 1.47이었고 재촬영에서 각각 1.90, 1.47, 1.80, 1.79, 1.53으로 모든 항목에서 더 진행하였다. 재촬영 상 점수가 증가한 증례는 III군에서 11예(78%)로 가장 많았고 추간판 항목에서만 의미있게 진행하였다. 결 론: 퇴행성 요추 질환의 보존적 치료 중 추시 MRI 촬영은 신경학적 증상이 악화되는 경우에 유용하였으며, 단순히 기존 증상의 호전이 없거나 통증의 정도만 증가한 경우에는 재촬영의 의미가 없었다. Purpose: This study examined the value and indications of repeated MRI in degenerative lumbar diseases under conservative management by comparing the primary MR and repeated MR images with respect to the symptomatic and radiological changes. Materials and Methods: Seventy patients with degenerative lumbar disease under conservative management underwent repeat MRI. Five MRI findings, including disc, foramen, facet joint, nerve root, and ligamentum flavum, were used to examine the difference between the initial and repeat MRI. The severity was graded using a four-point scale for each item. The patients were divided into 3 groups in order to compare the radiological changes and symptomatic changes, as follows; Group I no change from the initial symptoms (38 cases), Group II aggravation of the initial pain (18 cases), and Group III aggravation of the initial neurology or the development of a new neurology (14 cases). Results: The mean scores of each item the disc, foramen, facet joint, nerve root and ligamentum flavum increased from 1.76, 1.31-1.79, 1.71, and 1.47, respectively, to 1.90, 1.47, 1.80, 1.79, and 1.53, respectively. Group III showed the greatest proportion of cases with an increasing grading score (78%, 11 cases) only the disc was significant. Conclusion: Repeat MRI in degenerative lumbar disease under conservative management was found to be valuable only in cases with aggravated neurological symptoms, and was not relevant in cases with persistent symptoms or aggravated pain alone. KCI Citation Count: 0